Analisis Risiko K3 Dengan Metode Hazard Identification Risk Assessment And Risk Control ( HIRARC ) Pada Proses Pembuatan Nuget Ayam Di CV. Pangan Berkah Sentosa: OHS Risk Analysis with Hazard Identification Risk Assessment And Risk Control (HIRARC) Method in the Process of Making Chicken Nuggets at CV. Pangan Berkah Sentosa - Latif, Dito Mustofa; Wira Ghani, Sulung Rahmawan; Kistofer, Terdy (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2025)
Occupational Safety and Health (K3) risk analysis is an important step in ensuring a safe and healthy work environment for workers. CV Pangan Berkah Sentosa is one of the companies operating in the frozen food industry and can be said to have implemented K3, improvements and evaluation are needed because several cases of work accidents are still found. To prevent work accidents and work-related diseases, this can be done by conducting a risk analysis. One method that can be used is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). This method consists of 3 (three) stages, namely hazard identification, risk assessment and risk control. Based on the research results, there are 30 potential hazards, of which 43.4% are hazards in the low risk category, 50% are hazards in the medium risk category, and 6.6% are hazards in the high risk category. Activities that have a high level of risk are the meat grinding process, the packaging process using automatic packaging equipment. Controls that can be carried out to reduce risks are by using personal protective equipment (PPE) for workers in accordance with the risk of danger faced by workers, providing work aids to minimize direct contact of workers' body organs with machine parts that have a high potential for danger.